2007
DOI: 10.1515/epoly.2007.7.1.1618
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanical Behavior of Isotactic Polypropylene Composites Filled with Silver Nanoparticles

Abstract: Isotactic polypropylene (PP) nanocomposites containing 0.1, 0.3, 0.5 and 1.0 wt % silver (Ag) nanoparticles were prepared via melt compounding in a twin-screw extruder followed by injection molding The effects of the Ag nanoparticle additions on the structure and mechanical behavior of PP were studied using DSC, WXRD, optical microscopy, tensile and Izod impact techniques. DSC and WXRD measurements showed that the addition of only 0.1 wt% Ag nanoparticles promote the formation of β-form PP. Further increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…However, the b-form crystal of iPP is a metastable phase which is occasionally observed as a minor crystal phase in iPP that tends to transform to a-form under mechanical to thermal stimulates [21,22,[24][25][26][27]. Although presence of the b-phase leads to lower modulus and yield strength in iPP, its excellent effects on enhancement of toughness, impact strength, and heat distortion temperature of iPP has attracted much attention from research and industrial applications [21][22][23][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the b-form crystal of iPP is a metastable phase which is occasionally observed as a minor crystal phase in iPP that tends to transform to a-form under mechanical to thermal stimulates [21,22,[24][25][26][27]. Although presence of the b-phase leads to lower modulus and yield strength in iPP, its excellent effects on enhancement of toughness, impact strength, and heat distortion temperature of iPP has attracted much attention from research and industrial applications [21][22][23][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal crystallization, quenching, large temperature gradient, shear-induced crystallization, and addition of extrinsic b-nucleating agents, other polymers or inorganic fillers may cause to formation of b-phase crystals in iPP [22,23,27,[29][30][31][32][33]. Addition of selective b-nucleating agents, which are generally crystallizable organic compounds with low molecular weight (e.g., quinacridone dye, triphenodithiazine, and pimelic acid), is the common method to obtain high b-phase content in iPP [20,22,23,26,27,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, the nucleation of iPP crystallization by different nanoparticles was studied 3–9. It was found that exfoliated organo‐modified monmorillonite (o‐MMT) weakly nucleated the iPP crystallization 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…A stronger effect was described by Jain et al8 In iPP with 0.5–1 wt % of SiO 2 particles having sizes in the range of 30–80 nm, an increase of the iPP crystallization temperature by 7 °C was evidenced. A total of 0.1–1 wt % of silver nanoparticles dispersed in iPP caused elevation of the crystallization temperature by 4 °C 9. One notes that addition of 0.2–0.5 wt % of an efficient nucleating agent, sorbitol derivative, increases the iPP crystallization temperature much stronger, by ∼ 18 °C during cooling at 10 °C/min 10.…”
Section: Introductionmentioning
confidence: 99%